Pelatihan Programming Bagi Siswa SMA-IT Al Auliya Balikpapan Untuk Persiapan dalam Kompetisi Olimpiade Sains Nasional - Ihsan, Ihsan; Yanti, Nur; Lesmideyarti, Dwi; Rachman, Fathur Zaini; Zulkarnain, Zulkarnain (Universitas Negeri Gorontalo, 2024)
This activity was carried out with the background of wanting to implement relevant science to help problems in society. The world of education from elementary school to college is required to adapt to the rapid development of science, especially in the field of information technology. The purpose of this activity is in line with the holding of the Balikpapan City National Science Olympiad competition in the field of informatics, namely the material is basic programming language. So our Community Service Team will provide intensive training to students selected by the school to take part in the Balikpapan City OSN. The methods we use in the community service activities carried out by the team consist of building communication with partners, designing basic programming language learning modules, and providing training in the use of Dev C++ software in the form of training in installation and application in basic programming language coding and its implementation in everyday life in accordance with the National Science Olympiad curriculum. In implementing this Community Service, the PkM activity implementation team provides basic programming training, using a repetitive delivery method. This is because SMAIT AL Auliya students have never received material related to programming languages before at the high school level. Learning programming languages is something new for these students. So the implementation team must use the right learning strategy to deliver the material by creating presentation slides, teaching modules, practice questions and their discussions. So that the results of this activity get satisfactory results.